2019
DOI: 10.1177/0961000619836716
|View full text |Cite
|
Sign up to set email alerts
|

National culture and trust in online health information

Abstract: This article contributes to the ever-increasing body of research on online health information-seeking behaviour. Specifically, this study shows that national culture is a determinant of trust in online health information. A questionnaire-based survey collected the data from undergraduate students on the factors influencing their trust formation toward online health information. The cultural comparisons revealed differences between the trust formations of Americans, Chinese and South Koreans in the online healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 223 publications
(355 reference statements)
1
7
0
Order By: Relevance
“…It appeared as a universal promotor of HISB regardless of media type and topic of information. However, health information trust is too narrow compared with trust measures used in social capital studies and it is determined by national culture [ 87 ]. Therefore, we call for future studies which apply trust measures originated from social capital realm and based on different culture contexts to better understand the impact of trust.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared as a universal promotor of HISB regardless of media type and topic of information. However, health information trust is too narrow compared with trust measures used in social capital studies and it is determined by national culture [ 87 ]. Therefore, we call for future studies which apply trust measures originated from social capital realm and based on different culture contexts to better understand the impact of trust.…”
Section: Discussionmentioning
confidence: 99%
“…Culture may be an important factor in health communication involving risk. Different cultures put weight on different factors when making decisions about trust and credibility of information (Khosrowjerdi, 2019). One study comparing Koreans, Hongkongers and Americans showed that while trust in scientific authorities was consistent across all groups, Koreans and Hongkongers put more trust in experience-based health information (i.e.…”
Section: Political Ideology Has Probably Been One Of the Best Studied Individual Factors Much Of Gordonmentioning
confidence: 99%
“…Health information (Chu et al, 2018; Gao et al, 2015; Huntington et al, 2007; Jung et al, 2016; Khosrowjerdi, 2019; Kim et al, 1999; Liew, 2011; Yang and Beatty, 2016);…”
Section: Research Backgroundmentioning
confidence: 99%
“…Most of the studies employed computational and quantitative approaches (e.g. Chu et al, 2018; Gao et al, 2015; Khosrowjerdi, 2019; Mansour, 2018; Shen et al, 2019; Sohn and Choi, 2019), applied qualitative methods (e.g. Cader, 2013; Madden et al, 2012; O’Reilly and Marx, 2011) or mixed methods (e.g.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation